Manfaat Komputer Dalam Proses Pembelajaran Di STMIK BINA ADINATA Bulukumba - Muh Nasrun (Almeera Education, 2022)
This research is a research and development research and development, which was carried out at the STMIK Bina Adinata Campus. The design of this research is descriptive research, namely research that describes events as they are, with the aim of knowing the benefits of computers in the learning process of STMIK Bina Adinata Bulukumba. The population in this study were students of STMIK Bina Adinata Informatics Study Program, who programmed 38 professional ethics courses. The sampling technique used in this study is a total or census sampling technique. The determination of the sample in this study was determined by total sample, meaning that the entire population could be used as a sample, namely 38 people. Data collection techniques used in this study were observation, documentation and questionnaires. To find out the benefits of Variable X with Variable Y, it can be measured using the product moment correlation data analysis technique. Based on the results of this study with a significant level of 5% and N = 38, it turns out that the limit for rejection of Ho in table r is 0.257. The calculated r xy value = 0.961 in fact > from r xy table = 0.257 meaning the calculated r xy value is significant, so Ho is rejected and H1 is accepted, meaning that there are benefits of computers in the learning process at STMIK Bina Adinata Bulukumba